Heteropoda fischeri jager, 2005: A huntsman spider hunting on fellow cavernicoles in the caves of Meghalaya, India - Biswas, Jayant; Biswas, Siddharth (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.